Rendering with mental ray and 3ds Max. - van der Steen, Joep, ....-; Boardman, Ted, ....- (Amsterdam : Elsevier, 2010)
Create stunning renders of your 3ds Max models in mental ray with this concise guide. Learn all of the essential concepts such as indirect illumination, materials, render options, shaders, and lighting. Rendering with mental ray and 3ds Max, Second Edition is now revised to cover Autodesk Revit and special effects. The companion website includes all of the necessary project files from inside the book. *Render beautiful scenes with 3ds Max and the powerful mental ray application *Covers all aspects of rendering including materials, lighting, shaders, indirect illumination, and special effects *Companion website includes tutorial files and sample files